Exploring Hydraulic Behavior of Weir Using HEC-RAS at Semangir River Jember Regency - Retnaningtias, Sefti Aryani; Hidayah, Entin; Halik, Gusfan (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2025)
Flooding significantly impacts communities living along riverbanks, causing severe damage to infrastructure and properties. The flood event on January 9, 2022, in Bumi Mangli Permai and Mangli Residence Housing, heavily damaged access roads. Effective flood control is essential to mitigate these risks, and one viable solution is the implementation of long storage systems, particularly motion weirs. This study explores the hydraulic behavior of the Semangir River in Jember Regency using the HEC-RAS program to model both fixed and motion weirs. Utilizing the SUH Nakayasu method, peak discharges for 25-year, 50-year, and 100-year return periods were estimated. The analysis revealed that the existing weir's design is inadequate for the 50-year return period. However, simulations indicate that a motion weir with gate dimensions of 1.5 m x 1.75 m offers improved hydraulic conditions, reducing water surface elevation and flow velocity compared to both the existing and initially planned weirs. These findings support the adoption of motion weirs as an effective flood control strategy for the Semangir River.